2021
DOI: 10.3389/fimmu.2021.659184
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Myeloid Signature Genes in Head and Neck Squamous Cell Carcinoma to Predict the Prognosis and Immune Infiltration

Abstract: Myeloid cells are a major heterogeneous cell population in the tumor immune microenvironment (TIME). Imbalance of myeloid response remains a major obstacle to a favorable prognosis and successful immune therapy. Therefore, we aimed to construct a risk model to evaluate the myeloid contexture, which may facilitate the prediction of prognosis and immune infiltration in patients with head and neck squamous cell carcinoma (HNSCC). In our study, six myeloid signature genes (including CCL13, CCR7, CD276, IL1B, LYVE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 79 publications
2
9
0
Order By: Relevance
“…Then a novel prognostic gene signature was developed and validated by the TCGA and ICGC dataset. Similar to our results, another myeloid cell marker gene related gene signature was proved to be prognostic and predictive of immunotherapy response for patients with HNSCC ( Liu et al, 2021 ). Further, the risk score was proved to be correlated with tumor grade and stage.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Then a novel prognostic gene signature was developed and validated by the TCGA and ICGC dataset. Similar to our results, another myeloid cell marker gene related gene signature was proved to be prognostic and predictive of immunotherapy response for patients with HNSCC ( Liu et al, 2021 ). Further, the risk score was proved to be correlated with tumor grade and stage.…”
Section: Discussionsupporting
confidence: 89%
“…Through high-throughput sequencing technologies, we are now able to perform analysis to comprehensively catalog myeloid cells related genes in cancers. Liu et al developed a myeloid cells related gene signature containing 5 genes, which was valuable in evaluating the prognosis and immunity for head and neck squamous cell carcinoma ( Liu et al, 2021 ). However, their myeloid signature genes were generated from published literature of various tumors.…”
Section: Introductionmentioning
confidence: 99%
“…The up-regulation of CCL13 (a member of the CCL chemokine family) was also associated with the development of rheumatoid arthritis and [ 56 ] and cancer progression [ 57 ]. A prognostic risk model has identified CCL13 as a risk factor for poor prognosis of HNSCC patients [ 58 ]. In our study, we confirmed CCL13 promoted OSCC metastasis in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other clinical attributes (stage, grade, sex, and age), the risk score for forecasting 1‐, 3‐, and 5‐year survival status of HNSCC had higher AUC values, which was also higher than the previous models. 41 , 42 , 43 In addition, a higher risk score was considerably linked to older age, lymph node metastasis, and advanced stages, indicating that the risk score was more effective to stratify a patient's survival status. An ideal cut‐off point for model fitting was obtained using the Youden index rather than differentiating the risk merely premised on the median value.…”
Section: Discussionmentioning
confidence: 99%